Tax Compliance Determinants in a Challenging Fiscal Environment: Evidence from a Greek Experiment - Skoura V. Angeliki; Dasaklis K. Thomas (International Journal of Financial Studies)
This study investigates the factors influencing tax compliance among Greek entrepreneurs functioning within a difficult fiscal landscape. Through a randomized field experiment, we analyze the effects of differing tax rates, audit likelihoods, and legal frameworks on compliance behavior. Utilizing regression analysis alongside robustness checks, our results indicate that greater transparency in audits and customized penalty systems markedly improve compliance rates. These findings highlight the critical role of cultural and regulatory elements in determining taxpayer conduct and provide valuable insights for policymakers in both national and international tax systems. This study contributes to the ongoing discourse surrounding tax evasion and compliance, positioning Greece as a potential reference point for comparable economies in the European Union.